An application of the value tree analysis methodology within the integrated risk informed decision making for the nuclear facilities. (July 2015) - Borysiewicz, Mieczysław; Kowal, Karol; Potempski, Sławomir
Abstract: A new framework of integrated risk informed decision making (IRIDM) has been recently developed in order to improve the risk management of the nuclear facilities. IRIDM is a process in which qualitatively different inputs, corresponding to different types of risk, are jointly taken into account. However, the relative importance of the IRIDM inputs and their influence on the decision to be made is difficult to be determined quantitatively. An improvement of this situation can be achieved by application of the Value Tree Analysis (VTA) methods. The aim of this article is to present the VTA methodology in the context of its potential usage in the decision making on nuclear facilities. The benefits of the VTA application within the IRIDM process were identified while making the decision on fuel conversion of the research reactor MARIA. Highlights: New approach to risk informed decision making on nuclear facilities was postulated. Value tree diagram was developed for decision processes on nuclear installations. An experiment was performed to compare the new approach with the standard one. Benefits of the new approach were reached in fuel conversion of a research reactor. The new approach makes the decision making process more transparent and auditable.